Determination of Female Gender by Value of Maxillary Sinus Morphology using Digital Radiography - Younas Khan, Sadia Syed, Sadia Rafiq, Mohammad Asif Shahab, Muneeba Mughal, Siraj Ahmad (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine gender through digital radiography from the height and width of maxillary sinus. Study Design: Descriptive study. Place and duration of study: Kuwait Teaching Hospital and Khyber Teaching Hospital Peshawar from 1st January 2020 to 30th June 2020. Methodology: AP view of radiographs of 64 female participants was used and analysis of morphological parameters of maxillary sinus was done by using microdicom software. Results: The mean height and width of right maxillary sinus was 22.39mm and 22.54mm respectively while the mean height and width of left maxillary sinus was 22.39mm and 20.81mm respectively and was found to be statistically highly significant. Conclusion: Determination of female gender can be done with the help of anteroposterior view of digital radiographs from the height and breadth of maxillary sinuses. Key words: Gender determination, Forensic radiography, Female, Sexual dimorphism, Maxillary sinus